2013
DOI: 10.1159/000355515
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Alterations in Salivary Cortisol Levels in Pubertal Intracytoplasmic Sperm Injection Offspring

Abstract: Background: There is accumulating evidence that in vitro conception in humans may be associated with adverse health outcomes later in life. It has been proposed that suboptimal early life conditions may ‘program' key endocrine systems. A disturbance of the hypothalamic-pituitary-adrenal (HPA) axis leading to alterations in cortisol secretion in the offspring may be such a mechanism. To date, no data on cortisol levels in children conceived by intracytoplasmic sperm injection (ICSI) are available in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Further studies are needed to investigate this observation. The decreased levels of cortisol in the ICSI compared to the NC group within the subset of girls analyzed using metabolomics is consistent with a recent publication reporting lower salivary cortisol levels in the ICSI-conceived girls [33]. Moreover, there is growing evidence of hypothalamo-pituitary-adrenal axis dysfunction and blunted cortisol response in children born preterm or small for gestational age [34][35].…”
Section: Discussionsupporting
confidence: 88%
“…Further studies are needed to investigate this observation. The decreased levels of cortisol in the ICSI compared to the NC group within the subset of girls analyzed using metabolomics is consistent with a recent publication reporting lower salivary cortisol levels in the ICSI-conceived girls [33]. Moreover, there is growing evidence of hypothalamo-pituitary-adrenal axis dysfunction and blunted cortisol response in children born preterm or small for gestational age [34][35].…”
Section: Discussionsupporting
confidence: 88%
“…Glucocorticoids are important mediators of obesity and insulin resistance, and disruption of the hypothalamic–pituitary–adrenal axis has been proposed as a mechanism for unfavorable metabolic outcomes after in vitro conception (Belva et al ., ). Interestingly, lower salivary and serum cortisol levels have been reported in ICSI‐conceived girls compared to SC girls, although these results were based on single measurements (Belva et al ., ; Gkourogianni et al ., ). Mean salivary cortisol in the Belgium cohort was lower in ICSI‐conceived girls, which remained after adjusting for current characteristics, and early life and maternal factors (Belva et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, lower salivary and serum cortisol levels have been reported in ICSI‐conceived girls compared to SC girls, although these results were based on single measurements (Belva et al ., ; Gkourogianni et al ., ). Mean salivary cortisol in the Belgium cohort was lower in ICSI‐conceived girls, which remained after adjusting for current characteristics, and early life and maternal factors (Belva et al ., ). In a smaller cohort, an extensive review of plasma metabolomics also revealed lower cortisol levels in a subgroup of ICSI‐conceived girls aged 4 to 9 years compared to SC girls, alongside significant differences in 36 metabolites indicating early insulin resistance in the ICSI group (Gkourogianni et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations